"Sanningens ögonblick" : En uppsats om organisationsprinciper och deras betydelse för kundorienteringen hos folkbibliotek - Lindgren,Mikael (2002)
In writing this study, I wanted to examine which principles of organization that are possible for Swedish public libraries to use, and what these principles mean for the libraries customerorientation. This is done by examining a number of written sources, as well as studying the organization of six public libraries. I found several possible principles, but a number of principles have been more commonly used than others. Historically most public libraries were organized according to the functions needed to be carried out within the organization, but today it is much more common to use subject-based organizations, with some examples of organizing according to user-groups and needs. I have also encountered the possibility of organizing according to the sources that are to be handled, or the way in which these sources are used by the customers. The focus of subject-based organizations is the knowledge needed in order to satisfy the customers requirements, i. e. necessary for the evaluation of which sources that are to be presented to the customers. By identifying specific user-groups and their requirements it is possible for the library to provide a faster, more precise and adequate service. This can also be done by focusing on how different customer-groups is using the provided sources and services. I have found the last two organizational principles to be the best for the public libraries to use, in that they provide better foundation for the assessment and satisfaction of the customers requirements. These and the necessary knowledge then becomes the foundation of the organization, and exist in all parts of it.
Keywords: folkbibliotek; biblioteksorganisation; kundperspektiv; Documentation, information, library science, archivistics; Arkiv- och bibliotekskunskap, dokumentation